Fenomena penyimpangan penggunaan kata serapan di Kota Kolaka - Saadillah, Andi (Universitas Lampung, 2024)
Inappropriate use of foreign words in the public sphere often occurs for several reasons, including ignorance of the original meaning of the word, influence from the surrounding environment, or unintentional use. In Indonesian, sometimes foreign words are used inappropriately or not in accordance with the rules. One of the foreign languages absorbed into Indonesian is Arabic. The research method uses qualitative research. Qualitative descriptive research to analyze data in the form of foreign language absorption words whose absorption is not in accordance with the standard language rules of Indonesian. The research was conducted during the month of Ramadan 1445 H/2024 M so that the phenomenon of deviation of absorption words that appeared in the public domain of Kolaka City focused on Arabic foreign absorption words. The data were collected by observing, interview, documenting, and document review the absorption vocabulary contained in the data sources in the form of notice boards, posters, banners, pamphlets, billboards, billboards, and others. The results showed that the most common mistakes found in the public domain of Kolaka City are the words ramadan, salat, prayer, musholah, ummat, muslimah, sholawat, dzuhur, and wudu which should use the words ramadan, prayer, musala, ummah, muslimat, salawat, zuhur, and wudu. The findings of this study are expected to have a good impact on society about the importance of paying attention to the context and original meaning of the absorbing words used in communication. A good understanding of the language of origin of an absorbed word in the appropriate context. Thus, errors in the use of absorbing words can be minimized and effective communication can be maintained.Keywords: Phenomenon, Deviation, Adapted Words, Public Space